2012
DOI: 10.1007/s10751-012-0666-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite nanoparticles as-prepared and dispersed in Copaiba oil: study using magnetic measurements and Mössbauer spectroscopy

Abstract: and Mössbauer hyperfine parameters which were related to the interactions of Copaiba oil polar molecules with iron cations on magnetite nanoparticle's surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The EDS data recorded from our nominal samples lowering from 295 K down to low temperatures. Moreover, these spectra revealed asymmetrical six-line patterns with broad lines at 295 K and narrower lines at 90 and 21 K. As previously reported usual physical model accounting for the Iron cations at the tetrahedral (A) and octahedral [B] positions in magnetite cannot be used for a good spectra fit at the measured temperatures [16,17]. Therefore, as shown in Fig.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The EDS data recorded from our nominal samples lowering from 295 K down to low temperatures. Moreover, these spectra revealed asymmetrical six-line patterns with broad lines at 295 K and narrower lines at 90 and 21 K. As previously reported usual physical model accounting for the Iron cations at the tetrahedral (A) and octahedral [B] positions in magnetite cannot be used for a good spectra fit at the measured temperatures [16,17]. Therefore, as shown in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…(see examples in [6][7][8][9]). Recently it was shown that Mössbauer spectroscopy with a high velocity resolution opened up new possibilities of this technique in the study of various Iron containing materials (see [10][11][12][13][14] Iron oxide nanoparticles using Mössbauer spectroscopy with a high velocity resolution showed new results [15][16][17][18]. In this study we review the results obtained from the study of magnetite, maghemite and mixed maghemite/magnetite nanoparticles developed for magnetic fluids using Mössbauer spectroscopy with a high velocity resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Copaiba oil was collected from the Brazilian rainforest Copaifera tree ( Copaifera Langsdorffii Desf. ) and used for preparation of magnetic fluids [ 69 , 70 , 71 , 72 , 73 ]. TEM and HRTEM images of as-prepared Fe 3 O 4 nanoparticles are shown in Figure 30 .…”
Section: Nanoparticles In Biology Medicine and Pharmacymentioning
confidence: 99%
“…Adapted from Ref. [ 71 ] with permission from Springer Nature: Hyperfine Interactions, “Magnetite nanoparticles as-prepared and dispersed in Copaiba oil: Study using magnetic measurements and Mössbauer spectroscopy”, Oshtrakh M.I., Ushakov M.V., Semenova A.S., Kellerman D.G., Šepelák V., Rodriguez A.F.R., Semionkin V.A., Morais P.C., ©2013.…”
Section: Figurementioning
confidence: 99%